2021
DOI: 10.3727/105221621x16113475275710
|View full text |Cite
|
Sign up to set email alerts
|

Integrin Linked Kinase (ILK) and its Role in Liver Pathobiology

Abstract: Integrin Linked Kinase is a vital signaling protein ubiquitously expressed throughout the body. It binds to intracellular integrins to help promote signaling related to cell adhesion, apoptosis, proliferation, migration, and a plethora of other common cellular functions. In this review, ILK’s role in the liver is detailed. Studies have shown ILK to be a major participant in hepatic ECM organization, liver regeneration, insulin resistance, and hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…The profile comparison of lipid metabolism to humans also showed that known key elements like Fasn, Ilk, Ahsa1, Ughd, or Insig1 align with expression profiles from NASH, ALD, and HCC. These findings are also in line with recent literature, which associates these genes with liver diseases (36)(37)(38)(39).…”
Section: Multi-level Network Analysis Of Liver Tolerance Captures Hum...supporting
confidence: 93%
“…The profile comparison of lipid metabolism to humans also showed that known key elements like Fasn, Ilk, Ahsa1, Ughd, or Insig1 align with expression profiles from NASH, ALD, and HCC. These findings are also in line with recent literature, which associates these genes with liver diseases (36)(37)(38)(39).…”
Section: Multi-level Network Analysis Of Liver Tolerance Captures Hum...supporting
confidence: 93%
“…As a result of activating this signaling pathway, hepatic stellate cells (HSCs) become activated, motile, and synthesize more ECM components, including collagen type I, α-actin, and fibronectin ( Figure 5 C) [ 106 , 107 ]. Many cellular processes, including hepatocyte differentiation, growth, migration, and survival depend on ILK expression and its interaction with the extracellular matrix [ 108 ]. Researchers have shown that knocking down ILK results in dedifferentiated hepatocytes that can be regenerated by adding hydrated complex matrix preparations (Matrigel ® ), indicating that ILK contributes to maintaining extracellular microarchitecture.…”
Section: Resultsmentioning
confidence: 99%
“…The complex connects the ECM to the actin cytoskeleton and protects ILK from proteasomal degradation ( Legate et al, 2006 ). The ILK pathway is extensively involved in regulatory processes such as cell adhesion, apoptosis, proliferation, and migration ( Martucci et al, 2021 ). In cancer, ILK promotes EMT and enhances the migration and invasion of cancer cells ( McDonald and Dedhar, 2022 ).…”
Section: Ecm Stiffness-mediated Mechanical Signaling Pathwaymentioning
confidence: 99%
“…In cancer, ILK promotes EMT and enhances the migration and invasion of cancer cells ( McDonald and Dedhar, 2022 ). These cellular metabolism and behavior changes are facilitated by the activation of downstream signaling pathways such as AKT, Hippo, Wnt, and GSK-3β ( Martucci et al, 2021 ). ILK can promote the transition from fibroblasts to myofibroblasts in the dermis with the transcription factor Snail1/Slug ( Zoppi et al, 2018 ).…”
Section: Ecm Stiffness-mediated Mechanical Signaling Pathwaymentioning
confidence: 99%